The double role of GABAergic system in systemic tumors: an updated review - Yang, Xueyang; Zu, Qianhe; Wang, Luxuan; Li, Chunhui; Zhang, Lijian (Frontiers in Oncology, 2025)
The GABAergic system is the main inhibitory nervous system. In addition, GABA has been reported to affect tumor growth and its expression differs between tumor tissue and normal tissue. However, the impact of GABAergic system on tumor progression is context-dependent. The dual potential of the GABAergic system to exert either pro-tumor or anti-tumor effects is fundamentally shaped by the distinct histological features of the neoplasm. The complex components of the GABAergic system and signaling pathways involved might be responsible for this phenomenon. In this study, we reviewed the role of the GABAergic system in promoting or inhibiting tumorigenesis in different organ systems and summarized the possible signaling pathways regulated via GABAA receptor-associated protein (GABARAP). We also discussed the possible role of GABARAP in tumor progression through the regulation of autophagy. Additionally, this study suggest novel therapeutic approach targeting the GABAergic system in the treatment of tumors.